Magyar gazellák: Gyors növekedésű vállalatok jellemzői és kialakulásuk elemzése Magyarországon - Gábor Békés; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, 2011)
– This study analyses properties of fast growing small and medium sized firms, known as gazelles. Using balance sheet information for the 2000-2008 period, we show that a small fraction of companies is responsible for a large share of new jobs created in the business sector. For instance, the top 5% of fastest growing firms created 45.8% of new jobs, and 20% of new employment was generated by a mere 1% of firms. Importantly for policy, we show that the likelihood of becoming a gazelle is virtually the same in all industries and geographic regions. Using both probit regression and propensity score matching models, we show that younger firms with better financing background, more skilled labor force and better past growth performance are more likely to be gazelles. However, our model also shows that fast firm growth is highly idiosyncratic, and government or banks can not precisely predict which firm will actually turn into a gazelle.
Keywords: L25; D22; J23; 330; SME; firm growth; job creates; Unternehmenswachstum; KMU; Zweiter Arbeitsmarkt; Probit-Modell; Matching; Ungarn